Online testing method for 90-degree peel strength of bonding interface of bulk composite solid propellant block
By marking the sampling area on the side of the propellant block and conducting a 90° peel test, the problem of accurately measuring the bonding performance of large-volume composite solid propellant blocks was solved, achieving efficient, safe, and accurate online testing.
Patent Information
- Application Number
- CN202511825612.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-05
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies cannot accurately measure the bonding performance between large-volume composite solid propellant blocks and the coating insulation material interface. The test results of simulated specimens differ from the actual performance, making it impossible to test them directly on a standard material testing machine.
An online test method for the 90° peel strength of the bonding interface of large-volume composite solid propellant blocks was adopted. A rectangular sampling area was marked on the side of the block, a strip was cut and peeled off, and a fixture and tensile testing machine were used to continuously load the sample to ensure peel at a 90° angle. The peel load was recorded.
Online testing of the interface of large-volume composite solid propellant blocks has been achieved, improving testing efficiency, reducing labor intensity and safety hazards, and ensuring the accuracy and reliability of test results.
Smart Images

Figure CN121384787A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of propellant testing, in particular to a 90° peeling strength online testing method for the bonding interface of a large-volume composite solid propellant grain. BACKGROUND
[0002] At present, the main components of a solid rocket engine mainly include a shell, a solid propellant charge, an insulating layer, a nozzle and an ignition device. The solid propellant charge is usually in two forms: a free filling type and a shell bonding type. The free filling type charge needs to be previously made into a certain geometric shape of a grain coated with an insulating material and filled into the engine shell according to the shape. The shell bonding type charge is directly poured into the engine previously pasted with an insulating layer before solidification and cross-linking to be solidified and formed.
[0003] The interface bonding performance of the shell bonding type charge cannot be directly measured on the actual object, but can only be indirectly obtained by testing simulated test pieces according to GB / T 11211, QJ2038.1, QJ2038.2 and GB7760 standards, but there is a certain difference between the test results of the simulated test pieces and the actual bonding performance of the engine (different temperature, pressure and manufacturing process).
[0004] The single grain of the free filling type charge has a large volume, and in order to ensure that the grain column assembled by the single grains is stably combusted along the end surface and the engine works stably, the bonding performance between the single grain and the coated insulating material needs to be accurately measured. The single grain has a large volume, and the structure and size of each grain are different, so the sample cannot be directly clamped and tested on a standard material testing machine, and the standards (pulling, shearing and peeling) for testing the interface bonding performance are all tested on the standard material testing machine by using simulated interface process to make samples. The basic process of making the samples is to test the samples after bonding the measured material on the base plate and pressurizing and solidifying, and the making of the samples is limited by factors such as temperature, pressure, external forces such as mold closing and demolding, and cannot be consistent with the actual interlayer bonding performance, so as to accurately characterize the interlayer bonding performance of the actual object. Therefore, there is no standard test method for directly measuring the bonding performance of the large-volume special-shaped propellant grain and the coated insulating material, and the present application establishes a related test method, clearly defines the operation process and standardizes the operation standard, which is used for guiding the quality control and monitoring of the interface bonding performance (peeling test) of the large solid engine grain. SUMMARY
[0005] In view of the above problems, the 90° peeling strength online testing method for the bonding interface of a large-volume composite solid propellant grain can be online tested, and can guide the quality control and monitoring of the interface bonding performance (peeling test) of the large solid engine grain.
[0006] The technical scheme of the present application is an online testing method for 90° peeling strength of a large-volume composite solid propellant grain bonding interface, comprising the following steps: S1, sampling Marking a rectangular sampling area on the side surface of the grain, with the length direction being in the horizontal direction between the burning surface and the back arc surface of the grain; S2, cutting along the sampling area using a cutting tool, the cutting depth being to penetrate the cladding layer thermal insulation material and the lining layer of the grain, and not to scratch the grain surface, and the end of the rectangular sampling area close to the back arc surface is not cut; S3, peeling the cut sample from the burning surface to the back arc surface by 15-20 mm in length to form a free end, folding the free end to 90° angle and clamping it with a clamp so that the free end is at a 90° angle with the rest of the sample and the grain, and the clamp is also connected to a tensile testing machine; S4, starting the tensile testing machine to continuously load and peel, while controlling the clamp connected to the sample to move at the same speed and in the same direction as the peeling displacement in the horizontal direction to ensure that the peeling angle is controlled at 90°, until the sample and the grain are peeled apart, and the peeling load is recorded.
[0007] Further, the length of the rectangular sampling area is 55-70 mm, and the width is 20-30 mm.
[0008] Further, for a straight cylinder section grain, the rectangular sampling area is 300-500 mm away from the top surface of the grain; for a head section grain, the rectangular sampling area is 50-100 mm away from the top surface of the grain.
[0009] Further, in S2, the cutting depth is controlled to be less than 6 mm; and the cutting is prevented from frequent reciprocating to ensure that the cutting seam is straight, and the edge has no cutting or scratching defects.
[0010] Further, in S3, the free end is cleaned before being connected to the clamp, and the cleaning tool avoids contacting the grain surface.
[0011] Further, in S4, the tensile testing machine is controlled at a speed of 100 mm / min±5 mm / min, and the peeling length is more than 40 mm.
[0012] Further, the peeling load value is calculated from 5-10 mm after the initial peak value of the sample peeling, and the effective length should be not less than 30 mm.
[0013] Further, the peeling load is evaluated by the average peeling strength, and the calculation formula is ; in the formula, T is the average peeling strength, in units of N / mm; P B is the average value of the read peeling load, in units of N; b is the sample width, in units of mm; and the test result is rounded to two decimal places.
[0014] Further, record the sample damage type after peeling, respectively: J - interlayer damage of the thermal insulation material; B - interlayer damage of the liner material; Y - interlayer damage of the propellant; JB - interlayer damage between the thermal insulation layer and the liner; YB - interlayer damage between the propellant and the liner.
[0015] Further, each of the two sides of the drug block is tested once, and the sampling area of the side of the same batch of drug blocks is consistent; the drug block is cut after being placed at an ambient condition of 23℃±2℃ and a relative humidity of ≤70%RH for 2h, and is adjusted for at least 0.5h under the same ambient condition after being cut for testing.
[0016] The present application has the following beneficial effects: The present application has the following beneficial effects: The present application has the following beneficial effects:
[0017] Figure 1 It is a schematic diagram of the sampling position of the peeling sample; Figure 2 It is a detailed diagram of the sample size; Figure 3 It is a diagram of the clamping state of the sample; Figure 4 It is a diagram of the connection of the sample clamp; Figure 5 It is a schematic diagram of peeling curve calculation; Figure 6 It is a schematic diagram of on-site online peeling test; Figure 7 It is a schematic diagram of on-site online peeling test of different damage adhesive interfaces. DETAILED DESCRIPTION
[0018] The experimental methods in the following examples are all conventional methods unless otherwise specified. The raw materials or reagents used are all commercially available materials unless otherwise specified. The embodiments of the present application will be described in detail below in combination with examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be regarded as limiting the scope of the present application.
[0019] An online testing method for 90° peeling strength of a large-volume composite solid propellant grain bonding interface, comprising the following steps: S1, sampling Marking a rectangular sampling area on the side surface of the grain, with the length direction being in the horizontal direction between the burning surface and the back surface of the grain; S2, cutting the sampling area with a cutting tool, the cutting depth being sufficient to penetrate the thermal insulation material and the backing layer of the grain, and the cutting not damaging the grain surface, and the end of the rectangular sampling area close to the back surface not being cut; S3, peeling the cut sample from the burning surface to the back surface by 15-20 mm to form a free end, and then turning the free end to 90° and clamping it with a clamp so that the free end is at a 90° angle with the rest of the sample and the grain, and the clamp is connected to a tensile testing machine; S4, starting the tensile testing machine to continuously load and peel, while controlling the clamp connected to the sample to move at the same speed and in the same direction as the peeling displacement in the horizontal direction to ensure that the peeling angle is controlled at 90°, until the sample and the grain are peeled apart, and the peeling load is recorded.
[0020] In the selection of the sampling position, the present application samples on the side surface of the grain, which is beneficial to the continuous and constant stretching angle of the instrument in the later stage, and the side surface has the highest flatness to facilitate the control of the straightness of the cutting line when cutting and peeling the sample manually, and the side surface has the thinnest thermal insulation layer, which is beneficial to the maximum clamping force of the instrument clamp, and the sample is less likely to fall off during peeling test, avoiding online detection failure.
[0021] The same grain is sampled and tested twice, and the symmetrically equidistant positions on the two side surfaces are preferentially selected, so that the cutting and repairing positions of the grain remain the same, the repairing positions of the grains coincide when the grains are spliced, and the number of repairing positions distributed on the same horizontal position of the grain is the least; and the grains are ring-shaped and combined for loading, the repairing positions of different grains coincide under the secondary pressure of the ring-shaped external stress, the bonding performance of the repairing position is guaranteed, the interlayer erosion resistance of the repairing position is improved; after loading, the repairing positions are uniformly distributed on the same horizontal position of the grain, and the repairing positions ensure working at the same time period when the engine works along the end surface.
[0022] In the preferred scheme, the sampling area of the straight cylinder grain is 300-500 mm away from the top surface of the grain, more preferably 400 mm, as shown in Figure 1(a), the position is located between the upper and lower two sets of fastening points of the propellant block casting mold, the minimum point of the externally applied force, the theoretical minimum value of the interlayer bonding performance, which is used as the peeling detection point to effectively characterize the bonding performance of the whole propellant block; in addition, the position is located in the middle and upper position of the side surface of the propellant block, and the propellant block does not need to be moved and adjusted in height after demolding, is directly matched with the detection instrument, and the cutting and repairing position meets the ergonomics of workers, thereby reducing the labor intensity of the operators. Figure 1 (b), the position is the maximum operation position of the straight-line cutting of the peeling line; a certain distance from the top surface effectively avoids the thickest part of the upper and lower thermal insulation layer lap joint, is beneficial to the maximum occlusal force of the instrument clamp, and the sample piece is not easy to fall off during the peeling test, thereby avoiding the failure of online detection.
[0023] For the sample size, the length is 55-70 mm, and the width is 20-30 mm. Preferably, the length is 60 mm, and the width is 25±0.5 mm. See Figure 2 The method provided by the application directly performs peeling test on the propellant block, manual cutting of the thermal insulation layer needs to be performed, the propellant block is damaged to a certain extent, the sample size needs to ensure that the peeling test has sufficient peeling travel to filter the unstable collection of the sample at the start and end of the test, and the manual damage area of the propellant block is minimized. The repair area is minimized in the later period. The width parameter should not be too small, and the thermal insulation material is more prone to deformation during the peeling process, which causes distortion of the test result. The width parameter should not be too large, and the thermal insulation material needs to be applied with a larger external force to maintain a 90-degree right-angle deformation, and the test result is larger. The damage area of the propellant block is difficult to repair after being too large. During cutting, the depth is controlled to be less than 6 mm, the thickness of the thermal insulation coating layer is about 3 mm, the thickness of the lining layer is about 1-2 mm, and the thickness of the propellant block profile lap joint is about 4 mm. Controlling the depth of the cutting tool has a quantitative value control when the operator cuts, and ensures the standardization of the preparation of the peeling sample. The cutting seam depth should always penetrate the thermal insulation material, the lining layer, and the propellant block surface layer, and should not scratch the propellant block. Accurately exposing the weakest part of the lining layer under the application of external force, the interfacial bonding performance of the propellant block, and truly reflecting the ability of the propellant block interface to resist gas scouring. Controlling the cutting depth to be less than 6 mm requires the least manual operation control skill. During cutting, frequent reciprocating cutting is prevented, the cutting seam line is ensured to be straight, and the edge is free of cutting or scratching defects.
[0024] During cutting, the thermal insulation material and the lining layer are cut along the horizontal direction of the propellant block, but the length end of the cut thermal insulation material and the lining layer is connected with the whole coating material of the propellant block surface layer and should not be cut off, so as to ensure that the test sample does not completely separate from the main propellant block due to the test. After the peeling test is completed, the peeled coating material needs to be repaired in the original position and re-adhered to the propellant block.
[0025] Along the starting end surface of the peel sample, the width of the completed transverse cutting of the thermal insulation layer is controlled, and the split liner sample is peeled off from the combustion surface segment to the back arc surface direction by 15-20 mm in length to form a free end. Peeling off from the combustion surface segment to the back arc surface direction keeps consistent with the combustion direction of the engine end surface. The 15-20 mm peeled off has thermal insulation material overlap, which affects the accuracy of the test results, and will affect the maximum stroke not to be introduced into the peel displacement; ensure that the thermal insulation material and the clamp clamping reach a moderate area, ensure that there is enough biting force while not occupying too much peel displacement. The free end needs to be cleaned before being connected to the clamp, and the tool friction should be avoided during the cleaning process to prevent the propellant surface from generating heat, and the tool should not be in contact with the propellant surface at all times. The sample clamping state diagram is shown in Figure 3 , the unit is millimeter, 1 is the sample clamp; 2 is the liner layer, thermal insulation material interlayer of the propellant block surface; 3 is the propellant block.
[0026] Before the propellant block test, under the environmental conditions of 23℃±2℃ and relative humidity ≤70%RH, cut after standing for 2h, and the cut sample should be adjusted for at least 0.5h at standard temperature before testing. The difference between the propellant block and the environmental temperature is to achieve the purpose of consistency by prolonging the equilibrium time, reduce the influence of temperature on the peel load test, avoid the influence of humidity on the repair effect of peel damage, adjust the thermal insulation material for 0.5h when cutting, release and balance the deformation and stress generated, and ensure the accuracy of the peel test.
[0027] As shown in Figure 4 , the clamp connects the free end of the sample and the tensile testing machine, and loading is carried out through the tensile testing machine. At the same time, a horizontal moving shaft can be set to control the clamp connected to the sample to move in the same speed and direction as the peel displacement, so as to ensure that the peel angle is controlled at 90° angle, until the sample is completely separated, and the peel load is recorded. The control speed of the tensile testing machine is 100mm / min±5mm / min, and the interface peeling process mainly depends on the mechanical properties of the liner material. By studying the strain tensile curve of the liner itself, the tensile speed is determined to be 100mm / min. The breaking point of the sample appears after the yield point, the tensile strength is >1.5Mpa, and the elongation at break is >200%, which is ductile fracture, and the material has good flexibility. The actual process of propellant block liner spraying is combined with the high flow velocity of combustion gas to the propellant block interface during engine operation, and the liner material is subjected to high-speed shear force. The molecular chain of the material itself cannot stretch in time, and will break under a small amount of deformation. Therefore, the peel tensile rate needs to be kept at a high speed.
[0028] The peel load is read in the effective length, and the effective length of the peel curve is Figure 5Select, the effective length of the sample should be not less than 30 mm, and the peeling length of the sample corresponding to the effective length should be not less than 40 mm. The peeling load value is calculated from 5 mm to 10 mm after the initial peak of the sample peeling. The peeling stroke should be kept minimum (not less than 30 mm), and the damage area of the medicine block is minimized. At the same time, the stroke, time and force value collection frequency are matched optimally under high speed stretching. Figure 5 It can be seen that the peeling stroke from the starting point of stretching collection to the first peak is unstable, so the peeling load value is calculated from 5 mm to 10 mm after the initial peak of the sample peeling, and the result is more accurate.
[0029] The peeling test result indicates that the average peeling strength can be used for evaluation. The calculation formula is ; in the formula, T is the average peeling strength, unit N / mm; P B is the average value of the peeling load read, unit N; b is the sample width, unit mm; the test result is kept to 2 decimal places. The value of the general quality control index is greater than or equal to 2 N / mm.
[0030] After peeling, the sample damage type is recorded, which can be described by the following classification: J - interlayer damage of thermal insulation material; B - interlayer damage of lining material; Y - interlayer damage of propellant; JB - interlayer damage of thermal insulation layer and lining; YB - interlayer damage of propellant and lining.
[0031] The test result shows all the damage types of 2 samples (such as 1 "J", 1 "JB"), in which the ideal damage type is B, and YB is the allowed damage type.
[0032] The medicine block on-site online peeling test is shown in Figure 6 , and the test of different damage adhesive interfaces is shown in Figure 7 , in which a picture can observe that the peeling interface after damage is smooth and flat, which indicates that the two-phase interface does not bite each other, the peeling strength is low, and the adhesion is poor; b and c are damaged between different materials, b is damaged between the lining interfaces, and c is damaged between the lining and propellant two phases. It can be seen that the interface surface is uneven, which indicates that the two-phase interface penetrates and bites each other, the interface material is damaged obviously under the action of external force, the peeling strength is high, and the interface adhesion is good.
[0033] The different medicine blocks are tested online, and the specific conditions are shown in Table 1 and Table 2.
[0034] Table 1
[0035] Table 2
[0036] The effective peeling length in YK60 is slightly shorter, and the data difference between the two sides is larger, so the result is low in reference. The test results of the same drug block on both sides of YK49 have significant difference (1.87, 2.65), which indicates that the drug block has a problem, and the problem may be that the interface is caused by the comprehensive difference of solidification temperature, humidity and liner spraying thickness, resulting in poor bonding of single side interface.
[0037] The above examples describe the preferred embodiments of the present application, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other way. These simple modifications and combinations should also be considered as disclosed by the present application, and belong to the protection scope of the present application. Therefore, the protection scope of the present application patent should be subject to the appended claims.
Claims
1. An online testing method for the 90° peel strength of the bonding interface of a large-volume composite solid propellant block, characterized in that, Includes the following steps: S1. Sampling: Mark a rectangular sampling area on the side of the drug block, with its length direction located in the horizontal direction between the burning surface and the back arc surface of the drug block. S2. Use a cutting tool to cut along the sampling area. The cutting depth should be such that it penetrates the covering insulation material and lining of the drug block without scratching the drug surface. Do not cut the end of the rectangular sampling area near the back arc surface. S3. In the sampling area, peel off the cut sample strip from the burning side to the back arc side for a length of 15-20mm to form a free end. After the free end is turned to a 90° angle, it is clamped with a clamp so that the free end is at a 90° angle with the other sample strips and the drug block. The clamp is also connected to a tensile testing machine. S4. Turn on the tensile testing machine and continuously apply load to perform peeling. At the same time, control the clamp connected to the sample to move in the same direction and at the same speed as the peeling displacement in the horizontal direction, and ensure that the peeling angle is controlled at 90° until the sample and the drug block are peeled off. Record the peeling load.
2. The test method according to claim 1, characterized in that: The length of the rectangular sampling area is 55~70mm and the width is 20~30mm.
3. The test method according to claim 1, characterized in that: For cylindrical sections of explosive blocks, the rectangular sampling area should be 300-500 mm from the top surface of the block; for end-capped sections of explosive blocks, the rectangular sampling area should be 50-100 mm from the top surface of the block.
4. The test method according to claim 1, characterized in that: When cutting in S2, the depth should be controlled below 6mm; avoid frequent reciprocating cutting during cutting, and ensure that the cutting line is straight and the edge is free of cuts or scratches.
5. The test method according to claim 1, characterized in that: Before connecting the free end of the S3 to the fixture, it should be cleaned, and the cleaning tool should avoid contacting the surface of the drug block.
6. The test method according to any one of claims 1 to 5, characterized in that: The tensile testing machine in S4 has a controlled speed of 100mm / min ± 5mm / min and a peel length of 40mm or more.
7. The test method according to claim 6, characterized in that, The peel load value is calculated starting from 5mm to 10mm after the initial peak value of the peeled sample, and the effective length should be no less than 30mm.
8. The test method according to any one of claims 1 to 5, characterized in that: The peel load is evaluated using the average peel strength, and the calculation formula is as follows: In the formula: T is the average peel strength, in N / mm; P B b represents the average value of the peel load read, in N; b is the sample width, in mm; the test results are retained to two decimal places.
9. The test method according to any one of claims 1 to 5, characterized in that, After peeling, record the sample failure type as follows: J—Interlayer failure of thermal insulation material; B—Interlayer failure of lining material; Y – Propellant interlayer failure; JB – Damage between insulation layer and lining layer; YB – Propellant-liner failure.
10. The test method according to any one of claims 1 to 5, characterized in that: Each drug block was tested once on each of its two sides, and the sampling areas on the sides of the same batch of drug blocks were consistent. The drug blocks were placed in an environment of 23℃±2℃ and relative humidity ≤70%RH for 2 hours before being cut. After cutting, the blocks were conditioned under the same environmental conditions for at least 0.5 hours before testing.
